Japan from within : - Bryan, J. Ingram (T. F. Unwin ltd., 1924)
NY 1924 first edition Stokes. "An inquiry into the political, industrial, commercial, financial, agricultural, armamental and educational conditions of Modern Japan." Author was Professor in Japan for 16 years. Hardcover. Octavo, 288pp., index, cloth. Tiny red japanese mark on front end paper. Good, light wear, no DJ.